The Efficacy of Several Fungicides Against Root Rot Disease (Phytophthora capsici Leonian) on Pepper - Farriza Diyasti; Erwin Irawan Permana (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
Root rot disease caused by the fungus Phytophthora capsici can cause up to 60% yield loss of pepper in West Kalimantan, which is spread across Singkawang, Bengkayang, Pontianak, Sintang, and Sekadau Regencies. Control of BPB chemically with fungicide is considered to be effective enough to suppress BPB both in vitro and in the field. This study aims to examine the effectiveness of several fungicide active ingredients that are widely used in BPB control, namely Chlorotalonil, Azoxystrobin, Mankozeb, and Phosphoric Acid. Efficacy tests were carried out on sample plant plots consisting of 25 sample trees for each treatment of the active ingredient of the fungicide. Fungicide application was carried out 3 times (2-week intervals) within 3 months. BPB attack intensity was calculated to obtain the Efficacy Level (TE) category of the active ingredients used. The fungicide with the active ingredient phosphite acid showed the highest efficacy level of 30.06%, while the active ingredients Azoxystrobin and Mankozeb had TE values of 29.01% and 28.23%, respectively. The lowest result was the function with the active ingredient Chlorotalonil with a TE percentage of only 4.13%.